Doing Political Science on the Eve of Destruction: Why I Decided to Leave Academia - van der Does, Ramon (Politics of the Low Countries, 2025)
The current human condition knows no precedent. Our species’ history is replete with societies crumbling and ecosystems collapsing. But never before has human existence itself been this clearly on the eve of destruction. What does this mean for political science? In this piece, I argue why now more than ever political scientists ought to reflect on the question how they are to spend the 80,000 hours of their careers and explain my own choice to quit academia and do political science outside of the university.